Transcriptome Analysis and Sensory Evaluation of Thai Native Chicken Raised in Conventional and Free-Range Conditions - Seritrakul, P.; Poommarin, P. (Tropical Animal Science Journal, 2025)
Ethically raised animal products are believed to be better for both the environment and consumer health. Despite advances in chicken genetics and production systems, we still know little about how free-range condition affects the birds at a molecular level, specifically their gene expression and the resulting meat characteristics. This study aims to compare the transcriptome of Thai Praduhangdum, a native meat chicken raised in conventional floor pen and free-range systems, and investigate how these conditions cause gene expression changes at the molecular level and phenotypic changes in terms of meat sensory evaluation score. A total of 100 Thai Praduhangdum chickens were raised under a free-range system and a conventional floor pen system. At 6 months, blood samples were collected for transcriptome analysis and verified by quantitative real-time PCR. Additionally, meat samples were collected and sensory panel evaluation was performed. A total of 278 unique genes showed significantly different expression levels in either up-regulated or down-regulated direction. Gene set enrichment analysis revealed that these genes are associated with multicellular organism processes, development, and cell differentiation. Meat sensory panel evaluation showed that consumers preferred the appearance of the breast meat from the free-range chicken over the conventional floor pen chicken. Overall, the free-range condition caused detectable differences in gene expression and meat quality of Thai native chicken. The genes and pathways identified in this study provide a starting point for further functional tests and investigations into the relationship between chicken welfare and the physiological response at a molecular level.